2004
DOI: 10.1177/10883576040190010301
|View full text |Cite
|
Sign up to set email alerts
|

Joint Attention in Children With Autism

Abstract: Joint attention is an early-developing social-communicative skill in Which tWo people (usually a young child and an adult) use gestures and gaze to share attention With respect to interesting objects or events. This skill plays a critical role in social and language development. Impaired development of joint attention is a cardinal feature of children With autism, and thus it is important to develop this skill in early intervention efforts. Several interventions are described that involve teaching joint attent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 79 publications
1
91
0
5
Order By: Relevance
“…Research has shown significant differences across a variety of social communication deficits and restricted and repetitive behaviors when comparing individuals with ASD and typically developing individuals. Younger children with ASD often fail to naturally develop and demonstrate joint attention, an early form of social interaction typically observed between a parent and toddler [3,4]. Continued difficulties as the child develops are observed in reduced number of social initiations and reciprocity in conversation and sustained conversation skills, compared to typically developing school aged children [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown significant differences across a variety of social communication deficits and restricted and repetitive behaviors when comparing individuals with ASD and typically developing individuals. Younger children with ASD often fail to naturally develop and demonstrate joint attention, an early form of social interaction typically observed between a parent and toddler [3,4]. Continued difficulties as the child develops are observed in reduced number of social initiations and reciprocity in conversation and sustained conversation skills, compared to typically developing school aged children [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The request functions (on information and action) direct the child's behavior to the adult's demand and show the regulatory character of communication (BernardOptiz, 1982;Tjus et al, 2001). The use of showingoff function reveals that frequently the patients did not share the adult's attention focus, this way evidencing the sharing inability (Jones and Carr, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This ability, precociously acquired in normal development, presupposes that the child is willing to communicate his/her desire to the other through eye-gaze of the use of gestures (Jones and Carr, 2004). Affective exchanges occurring during adult-child interaction related to other referent (object or event) function as the basis to verbal communication which, by its turn, contributes to the improvement of the child's socialcognitive abilities (Bosa e Callias, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Such deficits are typically evident before one year of age (Jones & Carr, 2004) and have been associated with difficulties in subsequent language development (Mundy, Sigman & Kasari, 1990).…”
Section: Introductionmentioning
confidence: 99%